Penilaian Standar Mutu Pada Aplikasi Tiket Bioskop dengan ISO 27001 dan Fishbone Analisis - Ervin Setyawan; Farid Sukmana (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
Cinema ticket application services make it easy to purchase movie tickets. Various applications, especially in the business sector, certainly require information security that has been guaranteed to be applied and international information security certificates in ISO 27001 quality standards. Therefore, the requirements for obtaining information security certificates in international quality ISO 27001 need to be analyzed first. It requires a lot of preparedness that must be requested in meeting ISO 27001 quality standards. The purpose of this study is to analyze the application of cinema tickets for ISO 27001 eligibility. Analytical research methods used include clauses, checklists, Likert scales, maturity levels, and fishbone diagrams. The authors' references were based on the writer's team's analysis that the authors made, including graphs, charts, clause scores, checklist scores, Likert scales, maturity levels, and fishbone diagrams. Based on the author's analysis results, the cinema ticket application system does not meet ISO 27001 standards, so much needs to be improved in the system. Likert scale scores are still 19%, while to meet ISO 27001 standards, Likert scale scores must reach at least 60%. The overall problem with assessing this analysis, which results in cinema tickets being inappropriate or not passing ISO 27001 quality standards, is the lack of Likert scale scores and fishbone diagrams. This analytical research hypothesis can be the basis for future research that the application can meet the feasibility test of ISO 27001 quality standards.